FORMATION OF SEROUS FLUID (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Serous fluid or serum is a type of fluid that comes out of a wound with tissue damage. It is normal for a small amount of this clear fluid to leak from your wound. However, if you notice a lot of fluid coming out of your wound or if the fluid is thick like pus, contact a healthcare professional. A large amount of serous fluid or pus coming out of a wound may indicate the presence of a bacterial infection. This article will give you the skills and knowledge about the formation of serous fluid, treatment measures.